EFFECT OF GENDER AND DRIVER BEHAVIOR IN ROAD TRAFFIC CRASHES IN LAGOS STATE, NIGERIA - AUGUSTUS OROVWIGHO ATUBI (Social Sciences and Education Research Review)
Driver's behaviour is more complex when they are using the road. There are no universal guidelines for such behaviour. The research studied the effect of gender on driver behaviour in road traffic crashes in Lagos State. For data collection, a cross sectional research design was adopted. The data used in this study were collected from drivers in Lagos state through the use of a Driver Behaviour Questionnaire (DBQ) and Driver Skill Inventory (DSI), Survey between February, 2021 and March, 2022. Three thousand seven hundred (3,700) questionnaires were administered and 3,270 questionnaires were retrieved. The data generated were analysed using Chi-square tests, student't' test, analysis of variance (ANOVA) and the mann-whitney 'U' test statistics. These techniques were used to test the differences between male and female drivers on the driver behaviour (DBQ) and driver skill inventory (DSI) items. The study revealed that more than half of the studied drivers in Lagos State (66%) were men whereas (44%) were women. Also among the studied drivers, young drivers of the age group below 30 years (37.2%) were involved in accident crashes with a higher risk of involving in an accident. The analyses also showed that women reported a higher number of violations, and lapses. However, no significant association was found between male and female drivers in terms of errors. The results also showed that six (6) items of violations, three (3) items of lapses and three (3) items of error had significant association among male drivers as compared to female drivers in Lagos State. Based on the findings preventive measures are suggested to reduce the road accident crashes such as training and retraining of drivers, driver education, enforcement, seatbelts, speed limits etc.